THE EFFECT OF COMPETENCE, WORK ACHIEVEMENT, AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE AT THE OFFICE OF THE DPRD SECRETARIAT OF RIAU ISLANDS PROVINCE - Chevy Fantastic; Angelina E Rumengan; Sajiyo (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the influence of competence, work performance, and career development on employee performance with job satisfaction as an intervening variable at the Riau Islands Provincial DPRD Secretariat Office. This study uses a quantitative approach with a survey method and Structural Equation Modeling (SEM) analysis based on Partial Least Square (PLS). A sample of 150 employees was taken through a census. The results show that competence, work performance, and career development have a significant effect on performance. However, only career development has a significant effect on performance through job satisfaction. These findings provide important implications for human resource management in the government sector.